Experiences of early labour management from perspectives of women, labour companions and health professionals: a systematic review of qualitative evidence - Beake, Sarah; Chang, Yan-Shing; Cheyne, Helen; Spiby, Helen; Sandall, Jane; Bick, Debra (Elsevier, 2018)
Objectives: To examine evidence of women's, labour companions’ and health professionals’ experiences of management of early labour to consider how this could be enhanced to better reflect women's needs.